Survey of the endohelminth parasites of freshwater fishes in the upper Mezquital River Basin, Durango State, Mexico - de León, G. Pérez-Ponce; Rosas-Valdez, R.; Mendoza-Garfias, B.; Aguilar-Aguilar, R.; Falcón-Ordaz, J.; Garrido-Olvera, L.; Pérez-Rodríguez, R. (Zootaxa, 2009)
As a part of an ongoing inventory of the helminth parasites of freshwater fishes in Mexico, 676 specimens were collected between November 2007 and December 2008 in 23 localities along the upper Mezquital River Basin in Durango State, northern Mexico. Sixteen species of hosts, mostly corresponding to Nearctic freshwater elements, were studied. A total of 1,230 individual worms were collected during this survey, representing 25 species of endohelminths of which 9 were digeneans, 3 were cestodes, 4 were acanthocephalans, and 9 were nematodes. The checklist contains 24 new hosts and 42 new locality records. The information provided in this checklist may be helpful for our understanding of the biodiversity and historical biogeography of this host-parasite system, since the Mezquital River Basin mostly contains a Nearctic freshwater fish fauna, with a few Neotropical and endemic elements and may represent a transitional area from a biogeographical point of view.